Libros y lecturas durante la república liberal: Colombia, 1930-1946 - Silva, Renán (Sociedad y Economía, 2002)
In Colombia the República Liberal (1930-1946) attempted by diverse meansto bring the book to the popular classes, as an instrument of culture and recreation, and of modification of modes of doing and thinking which had been dominant along national history. In this area the main strategy was the Bibliotecas Aldeanas (Village Libraries) program. With a set of books they intended not only to difund the habit of reading among a population that was making inroads in literacy, but also to create in the small settlements some cultural institutions that would back up the tasks of cultural diffusion that were prompted by many other means, such as the movies, radio, etc. Results seem to have been meager and the initiative did not prosper in the long run. However, the effects upon the remaking of the cultural landscape of the popular classes should not be denied.